On the Equation Z(n) + SL(n) = n (The Chittagong University Journal of Science, 2021)
This paper considers the Diophantine equation Z(n) + SL(n) = n, where Z(n) is the pseudo Smarandache function and SL(n) is the Smarandache LCM function.The Chittagong Univ. J. Sci. 40(1) : 106-111, 2019